Theory of designing the gradient microstructured metals for overcoming strength-ductility trade-off. (15th July 2020) - Fan, Jitang; Zhu, Linli; Lu, Jian; Fu, Tao; Chen, Aiying
Abstract : Gradient microstructure design has been found to be an effective approach to significantly produce the utmost advanced structural metallic materials, which have a signature in mechanical characteristic of strength-ductility-hardenability combination. In this work, a physical theory and mechanism-based numerical model are developed for sophisticatedly designing the gradient microstructured metals. It considers the gradient distribution of grain size, twin, martensite and austenite in a metallic alloy. The numerical results are validated through experiments. The mechanical performance of high strength, large ductility and considerable hardenability is achieved and their trade-off is successfully overcome. Graphical abstract: Theory of designing the metals with a gradient microstructure involving grain size and volume fraction of austenite and martensite as well as twin space for overcoming strength-ductility trade-off with the mechanical performance of high strength, large ductility and considerable hardenability, which is validated by experiments. Image, graphical abstract